Penerapan Metode Preference Selection Index (PSI) Untuk Menentukan Maklon Skincare Terjangkau - Hidayatullah Al Islami; Rosyani, Perani (STMIK Budi Darma, 2024)
This research explores the utilization of the Preference Selection Index (PSI) method to determine affordable skincare contract manufacturers for skincare brands. The PSI method serves as a decision-making tool for multi-criteria analysis, enabling brands to establish their preferences regarding relevant criteria in selecting contract manufacturers. Data for this study were obtained through surveys and interviews with stakeholders in the skincare industry, along with relevant literature analysis. The findings indicate that the PSI method offers valuable insights into the process of identifying affordable skincare contract manufacturers, considering factors such as product quality, production capacity, and manufacturing costs. This research contributes to a better understanding of how skincare brands can utilize the PSI method to enhance efficiency and effectiveness in decision-making related to skincare product manufacturing. The practical implications of this study include assisting skincare brands in selecting manufacturers that meet their quality and financial criteria, thus enabling them to offer affordable skincare products to consumers.